Optimal Georeferenced Deployment of Charging Stations for Electric Vehicles in Distribution Networks Using a Trajectory-based Heuristic Model - Andaluz Salas, Miguel Alejandro (INGENIO, 2023)
The progressive increase in the consumption of fossil fuels and the constant efforts to reduce CO_2 emissions bring together the search for alternatives and the transport sector being one of the most dependent on fossil fuels and the cause of approximately 80% of the air pollution, the electric vehicle emerges as an alternative in mobility. That is why this article proposes a methodology for the optimal location of electric vehicle charging stations, given in a georeferenced distribution network scenario using a heuristic for the insertion of electric vehicles, taking into account energy consumption, travel and autonomy. developed based on real data, reducing the minimum location of charging stations. Evaluated in the distribution network of Santo Domingo-Ecuador, in a way that guarantees a technical and economic balance.